A microbiological approach to acne vulgaris. - Loveckova, Yvona; Havlikova, Ilona (Biomedical papers, 2002)
The present article gives a concise survey of contemporary opinions on acne vulgaris, its etiopathogenesis, clinical forms and laboratory diagnostics. In particular, the value of microbiological diagnostics and possibilities of local as well as general therapy are discussed. Moreover, our experience is described with vaccinotherapy to manage serious clinical forms and cases when current therapy fails.
Keywords: Acne vulgaris / Triglycerides / Propionibacterium / Hormones / Antibiotics / Isotretinoine / Vaccination